Time-resolved diffraction of shock-released SiO2 and diaplectic glass formation - A. E. Gleason (Nature Portfolio, 2017)
Our understanding of shock metamorphism and thus the collision of planetary bodies is limited by a dependence on ex situ analyses. Here, the authors perform in situ analysis on shocked-produced densified glass and show that estimates of impactor size based on traditional techniques are likely inflated.